Teaching Speaking Using Role Play Technique at Twelfth Grade in SMAN 2 Luwuk - Amaliya Yayang Safira; Yuliana Mangendre; Anwar Anwar (BABASAL English Education Journal, 2022)
This research is aimed to know whether the Role Play Technique is effective in improving students speaking skills among 12th-grade students of SMAN 2 Luwuk. This research was based on categorized as Experimental Research. It is carried out to solve students’ problems in speaking. The subject of this research is the students of class XII MIPA 2 and XII MIPA 3 of SMAN 2 Luwuk. In collecting the data, this research used a pretest and post-test. Based on the result and the discussion of this research, it can be said that the use of role-playing in teaching speaking was successful since the criteria of success were achieved. The criteria of success are there was a significant improvement from the pretest result to the posttest. The result showed that the pretest average score in the experimental class is 840 becomes 1,420 in the post-test while in the control class, the significant improvement is 760 in the pretest and 1,060 in the post-test. The degrees of freedom were 38, and the t-table obtained was 1.686. Through the pretest and posttest result, the t-counted results were obtained  level = 5% = 0,05, degrees of freedom (df) = 38 indicated than t-table value = 1.686 and the t-counted value = 2.135. It can be concluded that Ha is received and Ho is refused. It means that the use of the Role Play Technique can improve students’ speaking skills at SMA Negeri 2 Luwuk. Based on the result that is mentioned before, the researcher suggests that the English teacher should implement role play to improve students’ speaking skills.Keywords: Teaching Speaking, Roleplay